Semiotic Perspective of Characteristics and Meanings of Hunto Sultan Amai Mosque Ornaments in Gorontalo - Asmin Salongi; Afifah Harisah; Ria Wikantari (EPI International Journal of Engineering, 2022)
A mosque is a well-known form of architecture in the Islamic community, serving as a center for religious activities and a symbol of Islamic identity. The Hunto Mosque in Gorontalo City, Hohuntonga, which means a gathering place, is known for its beautiful architectural design which owes much to the role of the ornaments adorning the building. This research aims to describe and interpret the characteristics and meanings of the ornaments in the Hunto Sultan Amai Mosque, as well as identify the factors that shape their characteristics. A qualitative method with Roland Barthes' (1986) semiotic approach was employed, and data was gathered through observation, interviews, and documentation. The results reveal that the ornamentation in the mosque consists of geometric and floral shapes, with square patterns and lotus flower motifs, colored in white and gold and made of paint. The most prominent placement of these ornaments is on the mosque wall elements. The square shape has meaning “symbol of physical experience and the physical world of materiality”, while the lotus flower represents adaptation and idealism. White signifies purity, while gold symbolizes triumph and power. The characteristics and meanings of the ornaments are formed from Arab and Malay architecture.